Chasing the Break : Tracing the Full Evolution of a Black Hole X-Ray Binary Jet with Multiwavelength Spectral Modeling - Echiburú-Trujillo, Constanza (Institute of Physics Publishing, 2025)
Black hole (BH) X-ray binaries (XRBs) are ideal targets to study the connection between accretion inflow and jet outflow. Here we present quasi-simultaneous, multiwavelength observations of the Galactic BH system MAXI J1820+070, throughout its 2018-2019 outburst. Our data set includes coverage from the radio through X-ray bands from 17 different instruments/telescopes, and encompasses 19 epochs over a 7 month period, resulting in one of the most well-sampled multiwavelength data sets of a BH XRB outburst to date. With our data, we compile and model the broadband spectra of this source using a phenomenological model that includes emission from the jet, a companion star, and an accretion flow. This modeling allows us to track the evolution of the spectral break in the jet spectrum, a key observable that samples the jet launching region. We find that the spectral break location changes over at least approximate to 3 orders of magnitude in electromagnetic frequency over this period. Using these spectral break measurements, we link the full cycle of jet behavior, including the rising, quenching, and reignition, to the changing accretion flow properties as the source evolves through its different accretion states. Our analysis shows consistent jet behavior with other sources in similar phases of their outbursts, reinforcing the idea that jet quenching and recovery may be a global feature of BH XRB systems in outburst. Our results also provide valuable evidence supporting a close connection between the geometry of the inner accretion flow and the base of the jet.